Electroactive Materials for Metal-Ion Batteries

A porous carbon framework with nanoscale silicon domains addresses the volume change issues in silicon-based anodes, enhancing the stability and capacity retention of rechargeable metal ion batteries.

JP7600107B2Active Publication Date: 2024-12-16NEXEON LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021524988
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-09
Filing Date
2019-11-08
Publication Date
2024-12-16
Estimated Expiration
2039-11-08

AI Technical Summary

Technical Problem

Existing rechargeable metal ion batteries, particularly those using silicon as an anode material, face challenges with high volume changes during charging and discharging, leading to mechanical stress, delamination, and irreversible capacity loss due to insufficient solid electrolyte interface (SEI) formation, making them unsuitable for commercial use.

Method used

A composite material comprising a porous carbon framework with optimized micropores and mesopores, where nanoscale silicon domains are distributed within these pores, controlling the weight ratio of silicon to carbon to maintain structural stability and minimize SEI formation.

Benefits of technology

The composite material achieves high gravimetric and volumetric capacities with exceptional reversible capacity retention, accommodating silicon expansion without significant structural damage, thus improving the performance of rechargeable metal ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600107000005
    Figure 0007600107000005
  • Figure 0007600107000001
    Figure 0007600107000001
  • Figure 0007600107000002
    Figure 0007600107000002
Patent Text Reader

Abstract

The present invention provides a particulate electroactive material comprising a plurality of composite particles, the composite particles having an average particle size of (a) at least 0.7 cm 3 The present invention relates to a particulate electroactive material comprising: (a) a porous carbon skeleton comprising micropores and / or mesopores having a total volume of 1 / g, wherein at least half of the volume of the micropores / mesopores has the form of pores with a diameter of 5 nm or less; and (b) silicon located within the micropores and / or mesopores in a defined amount relative to the volume of the micropores and / or mesopores of the porous carbon skeleton.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates generally to electroactive materials suitable for use in electrodes for rechargeable metal-ion batteries, and more particularly to particulate materials having high electrochemical capacity suitable for use as anode active materials in rechargeable metal-ion batteries. [Background technology]

[0002] Rechargeable metal-ion batteries are widely used in portable electronic devices such as mobile phones and laptops, and are increasingly being applied in electric or hybrid vehicles. Rechargeable metal-ion batteries generally include an anode layer, a cathode layer, an electrolyte that transports metal ions between the anode and cathode layers, and an electrically insulating porous separator disposed between the anode and cathode. The cathode typically includes a metal current collector with a layer of metal ion containing metal oxide-based composite material, and the anode typically includes a metal current collector with a layer of electroactive material, defined herein as a material capable of inserting and releasing metal ions during charging and discharging the battery. For the avoidance of doubt, the terms "cathode" and "anode" are used herein in the sense that the battery is loaded such that the cathode is the positive electrode and the anode is the negative electrode. When the metal-ion battery is charged, metal ions are transported from the metal ion-containing cathode layer through the electrolyte to the anode and inserted into the anode material. The term "battery" is used herein to refer to both devices containing a single anode and a single cathode, and devices containing multiple anodes and / or multiple cathodes.

[0003] There is interest in improving the gravimetric and / or volumetric capacity of rechargeable metal-ion batteries. The use of lithium-ion batteries has already provided significant improvements over other battery technologies, but there is room for further development. To date, commercially available lithium-ion batteries have been primarily limited to the use of graphite as the anode active material. Upon charging a graphite anode, lithium is inserted between the graphite layers, resulting in a charge-discharge reaction with the empirical formula Li xC6, where x is greater than 0 and less than or equal to 1. As a result, graphite has a maximum theoretical capacity of 372 mAh / g in lithium-ion batteries, with practical capacities somewhat lower (approximately 340 mAh / g to 360 mAh / g). Other materials, such as silicon, tin, and germanium, can intercalate lithium at significantly higher capacities than graphite, but are not yet in widespread commercial use due to the difficulty of maintaining sufficient capacity over many charge-discharge cycles.

[0004] In particular, silicon has been recognized as a promising alternative to graphite in the manufacture of rechargeable metal-ion batteries with high gravimetric and volumetric capacities due to its extremely high capacity relative to lithium (see, for example, Non-Patent Document 1). Silicon has a theoretical maximum specific capacity of about 3600 mAh / g (Li ion battery) at room temperature. 15 However, the use of silicon as an anode material is complicated by its large volume change upon charging and discharging.

[0005] When lithium is intercalated into bulk silicon, the volume of the silicon material increases significantly, up to 400% of its original volume when the silicon is lithiated to its maximum capacity. Then, repeated charge-discharge cycles generate significant mechanical stresses in the silicon material, leading to fracture and delamination of the silicon anode material. The volumetric shrinkage of silicon particles upon delithiation can result in loss of electrical contact between the anode material and the current collector. To make matters even more difficult, the solid electrolyte interface (SEI) layer that forms on the silicon surface is not mechanically durable enough to accommodate the expansion and contraction of silicon. As a result, the newly exposed silicon surface leads to further decomposition of the electrolyte, an increase in the thickness of the SEI layer, and irreversible consumption of lithium. Collectively, these failure mechanisms result in unacceptable electrochemical capacity loss over successive charge-discharge cycles.

[0006] Numerous approaches have been proposed to overcome the problems associated with the volume changes observed during charging of silicon-containing anodes. The most prevalent approach to address irreversible capacity loss in silicon-containing anodes is the use of some form of microstructured silicon as the electroactive material. It has been reported that fine silicon structures with cross sections less than about 150 nm, such as silicon films and silicon nanoparticles, are more resistant to volume changes during charging and discharging compared to silicon particles in the micron size range. However, none of these are particularly suitable for commercial scale application without morphology modification. Nanoscale particles are difficult to manufacture and handle, and silicon films do not provide sufficient bulk capacitance. For example, nanoscale particles tend to form agglomerates, which makes it difficult to effectively disperse the particles within the anode material matrix. The formation of nanoscale particle agglomerates also results in unacceptable capacity loss during repeated charge-discharge cycles.

[0007] Ohara et al. (Non-Patent Document 2) described the deposition of silicon as a thin film on a nickel foil current collector and the use of this structure as the anode in a lithium-ion battery. Although this approach results in good capacity retention, the thin film structure does not have a useful amount of capacity per unit area, and any improvement is eliminated as the film thickness increases.

[0008] US Pat. No. 5,399,433 discloses that capacity retention can be improved by using silicon particles with a high aspect ratio, ie, the ratio of the maximum dimension to the minimum dimension of the particle.

[0009] It is also commonly known that electroactive materials such as silicon can be deposited within the pores of porous support materials such as activated carbon materials. These composites offer some of the beneficial charge-discharge properties of nanoscale silicon particles while avoiding the difficulties of handling nanoparticles. For example, Guo et al. (Non-Patent Document 3) disclose silicon-carbon composites in which a porous carbon substrate provides a conductive scaffold with silicon nanoparticles deposited uniformly distributed within the substrate's pore structure. The formation of the SEI during the first charge cycle is confined to the remaining pore volume such that the remaining silicon is not exposed to the electrolyte during subsequent charge cycles. The composites have been shown to improve capacity retention over multiple charge cycles, but the initial capacity of the composites in mAh / g is significantly lower than that for silicon nanoparticles.

[0010] US Patent No. 5,999,336 discloses an active material comprising a carbon-based scaffold having small pores branching off from a small number of larger pores. An electroactive material (e.g., silicon) is randomly located on the walls of both the large and small pores, as well as on the outer surface of the carbon-based scaffold.

[0011] Despite previous efforts, there is a continuing need to improve the electrochemical storage capacity of lithium-ion batteries. In particular, there remains a need to identify alternative silicon-based materials that offer the advantages of the high lithiation capacity of silicon, but that also have sufficient capacity retention and structural stability for use in commercially viable rechargeable batteries. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] International Publication No. 2007 / 083155 [Patent Document 2] JP 2003-100284 A [Non-patent literature]

[0013] [Non-Patent Document 1] Insertion Electrode Materials for Rechargeable Lithium Batteries, Winter, M. et al. in Adv. Mater. 1998, 10, No. 10 [Non-Patent Document 2] Journal of Power Sources 136 (2004) 303-306 [Non-Patent Document 3] Journal of Materials Chemistry A, 2013, pp. 14075-14079 Summary of the Invention [Problem to be solved by the invention]

[0014] The present invention is based on the discovery that the performance of a composite material comprising a porous carbon scaffold and silicon as an electroactive material located within the porous carbon scaffold can be optimized by using a porous carbon scaffold with a specific pore structure and a controlled ratio of silicon to available pore volume. [Means for solving the problem]

[0015] In a first aspect, the present invention provides a particulate material comprising a plurality of composite particles, the composite particles comprising: (a) a porous carbon framework containing micropores and / or mesopores, The micropores and mesopores have a total pore volume of P measured by gas adsorption. 1 cm 3 / g, where P 1 has a value of at least 0.7, PD measured by gas adsorption 50 a porous carbon skeleton having pores with a diameter of 5 nm or less; (b) a plurality of elemental nanoscale silicon domains located within the micropores and / or mesopores of the porous carbon framework; and Including, The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.5×P 1 ~1.3×P 1 ]:1.

[0016] The present invention therefore relates to particulate materials in which the porous carbon skeleton has a relatively high total volume of micropores and mesopores, with pores having a diameter of 5 nm or less constituting at least 50% of the total pore volume. 1 relates to the pore volume of the porous carbon skeleton when measured alone, i.e., without any silicon or other material occupying the pores of the porous carbon skeleton.

[0017] Elemental silicon is located in the micropores and / or mesopores in the form of a plurality of nanoscale silicon domains. As used herein, the term "nanoscale silicon domains" refers to nanoscale bodies of silicon located within the pores of the porous carbon skeleton. At least a portion of the nanoscale silicon domains are formed by the PD 50 The silicon occupies at least a portion of the mesopores and / or micropores having a diameter smaller than the pore size, and therefore has a dimension of 5 nm or less. The weight ratio of silicon to the porous carbon skeleton is [0.5×P 1 ~1.3×P 1 ]:1, which correlates with the total micropore / mesopore volume. 1 By defining the weight ratio of silicon based on the value of [0.5×P], the volume fraction of the pore volume occupied by silicon is controlled within a specific limit. In other words, when the weight ratio of silicon to the porous carbon skeleton is [0.5×P], the volume fraction of the pore volume occupied by silicon is controlled within a specific limit. 1 ~1.3×P 1 ]:1, the volume of silicon in the composite particles corresponds to approximately 20%-55% of the total micropore / mesopore volume of the porous carbon skeleton.

[0018] The present invention thus generally relates to particulate materials in which silicon partially occupies the pores of a highly porous carbon framework, the pore volume of which is predominantly in the form of small mesopores and / or micropores. This particulate structure has been found to provide electroactive materials with high gravimetric and volumetric capacities upon lithiation, and exhibits a unique ability to accommodate the expansion of silicon, thereby exhibiting high reversible capacity retention over multiple charge / discharge cycles.

[0019] The exceptional reversible capacity retention of the particulate materials of the present invention has been found to be associated with the high porosity of the porous carbon scaffold, the high proportion of small mesopores and / or micropores in the porous carbon scaffold, and the controlled loading of silicon in the composite relative to the total mesopore / micropore volume.

[0020] Without being bound by theory, it is believed that the nanoscale silicon domains located within the small mesopores and / or micropores first provide fine silicon structures that can be lithiated and delithiated without excessive structural stress. It is believed that these very fine silicon domains are less resistant to elastic deformation and more resistant to fracture than larger silicon structures. Secondly, by controlling the loading of silicon within the porous carbon skeleton such that only a portion of the pore volume is occupied by silicon in the uncharged state, the unoccupied pore volume of the porous carbon skeleton can accommodate a significant amount of silicon expansion within. More specifically, it is believed that the highly microporous carbon skeleton can be elastically deformed at a low fracture rate due to the thin pore walls, and that the tensile fracture strength of this skeleton is very high.

[0021] Thus, silicon's low resistance to elastic deformation works synergistically with carbon's relatively high elastic modulus to drive silicon expansion into the pore volume of the porous carbon skeleton. As silicon is further lithiated, the entire composite particle undergoes some external expansion, but the amount of external expansion is limited by the silicon expansion accommodating internally. Until the particle expands outward, the microporous structure of the porous carbon skeleton can deform without breaking. By carefully controlling the amount of internal and external expansion, the distortion of the porous carbon skeleton and silicon domains is limited to a level that can be tolerated over multiple charge-discharge cycles without significant loss of capacity. The high total porosity of the porous carbon skeleton not only provides high volumetric loading of silicon, but also ensures that the porous carbon skeleton is resilient enough to withstand repeated volume changes over multiple charge-discharge cycles.

[0022] Yet another factor in the extraordinary performance of the particulate material of the present invention is the minimization of SEI formation. As mentioned above, the nanoscale silicon domains are located within small mesopores and / or micropores, limiting the formation of SEI since only a small area of ​​the silicon surface is accessible to the electrolyte. Additional exposure of silicon during subsequent charge-discharge cycles is substantially prevented so that SEI formation is not a significant failure mechanism that can lead to capacity loss. This is in clear contrast to the excessive and unconstrained formation of SEI that is characteristic of the material disclosed by, for example, Guo (see above). Minimizing exposed silicon surface has the additional benefit of reducing oxidation of the silicon surface.

[0023] As a result of the unique particle structure of the particulate materials of the present invention, the silicon in the composite particles has electrochemical performance comparable to that of fine silicon nanoparticles, but without the disadvantages of excessive SEI formation and poor dispersity that make discrete silicon nanoparticles unviable as an electrode material for commercial use.

[0024] The porous carbon framework preferably comprises a three-dimensionally interconnected open pore network comprising a combination of micropores and / or mesopores, and optionally a small amount of macropores. In accordance with conventional IUPAC terminology, the term "micropores" is used herein to refer to pores with a diameter of less than 2 nm, the term "mesopores" is used herein to refer to pores with a diameter of 2 nm to 50 nm, and the term "macropores" is used herein to refer to pores with a diameter of more than 50 nm.

[0025] References herein to the volume of micropores, mesopores, and macropores within a porous carbon skeleton, as well as any reference to the pore volume distribution within a porous carbon skeleton, refer to the internal pore volume of the porous carbon skeleton alone (i.e., in the absence of silicon or other material occupying some or all of the pore volume).

[0026] The porous carbon framework is characterized by a high pore volume in the form of micropores and / or mesopores. As used herein, the total volume of micropores and mesopores (i.e., the total pore volume in the range of 0 nm to 50 nm) is defined as P 1 cm 3 / g, where P 1 represents a dimensionless natural number having a value of at least 0.7. 1 The value of is also used to correlate the effective pore volume in the porous carbon skeleton with the weight ratio of silicon to the porous carbon skeleton, as discussed above.

[0027] More preferably, P 1 Optionally, the value of P is at least 0.75, or at least 0.8, or at least 0.85. 1can be at least 0.9, or at least 0.95, or at least 1, e.g., at least 1.05, at least 1.1, at least 1.15, or at least 1.2. The use of a high porosity carbon skeleton is advantageous because it allows more silicon to be accommodated within the pore structure, and it has been found that a high porosity carbon skeleton, whose pore volume is primarily in the form of micropores and / or smaller mesopores, has sufficient strength to accommodate the volumetric expansion of silicon without the porous carbon skeleton breaking or otherwise degrading.

[0028] The internal pore volume of the porous carbon skeleton is preferably limited at a value where the increased fragility of the porous carbon skeleton outweighs the benefit of the increased pore volume accommodating a larger amount of silicon. 1 The value of P may be less than or equal to 2.5. However, more preferably, 1 The value of P may be 2.2 or less, or 2 or less, or 1.8 or less, or 1.6 or less, or 1.5 or less, or 1.4 or less, or 1.3 or less, or 1.2 or less, or 1.1 or less, or 1.0 or less, or 0.9 or less. More preferably, P 1 The value of is less than or equal to 1.2, or less than or equal to 1.1, or less than or equal to 1.0, or less than or equal to 0.9.

[0029] According to the present invention, P 1The value of is, for example, in the range of 0.8 to 2.2, or in the range of 0.85 to 2.2, or in the range of 0.9 to 2.2, or in the range of 0.95 to 2.2, or in the range of 1 to 2.2, or in the range of 1.05 to 2.2, or in the range of 1.1 to 2.2, or in the range of 0.8 to 2, or in the range of 0.85 to 2, or in the range of 0.9 to 2, or in the range of 0.95 to 2, or in the range of 1 to 2, or in the range of 1.05 to 2, or in the range of 1.1 to 2, or in the range of 0.8 to 1.9, or in the range of 0.85 to 1.9, or in the range of 0.9 to 1.9, or in the range of 0.95 to 1.9, or in the range of 1 to 1.9, or in the range of 1.05 to 1.9, or in the range of 1.1 to 1.9, or in the range of 0.8 to 1. The range of 0.8, or 0.85 to 1.8, or 0.9 to 1.8, or 0.95 to 1.8, or 1 to 1.8, or 1.05 to 1.8, or 1.1 to 1.8, or 0.8 to 1.7, or 0.85 to 1.7, or 0.9 to 1.7, or 0.95 to 1.7, or 1 to 1.7, or 1.05 to 1.7, or 1.1 to 1.7, or 0.8 to 1.6, or 0.85 to 1.6, or 0.9 to 1.6, or 0.95 to 1.6, or 1 to 1.6, or 1.05 to 1.6, or 1.1 to 1.6.

[0030] Preferably, P 1 The value can be, for example, in the range of 0.7 to 1.5, or in the range of 0.75 to 1.4, or in the range of 0.7 to 1.3, or in the range of 0.75 to 1.3, or in the range of 0.7 to 1.2, or in the range of 0.75 to 1.2, or in the range of 0.7 to 1, or in the range of 0.75 to 1, or in the range of 0.7 to 0.9, or in the range of 0.75 to 0.9.

[0031] PD of porous carbon frameworks 50 The pore size is less than 5 nm. 50 The term "pore size" refers to the median pore size on a volumetric basis based on the total volume of micropores and mesopores (i.e., the pore size less than or equal to the P 1(the pore size at which 50% of the total micropore and mesopore volume is present, represented by 1.0 mm). Thus, according to the invention, at least 50% of the total volume of the micropores and mesopores has the form of pores with a diameter of less than 5 nm.

[0032] As used herein, "PD n The general term "pore size" refers to the nth percentile pore size on a volume basis based on the total volume of micropores and mesopores. For example, "D 90 The term "pore size" refers to the size of the pores that are smaller than the P 1 (Refers to the pore size at which 90% of the total micropore and mesopore volume is present, represented by

[0033] For the avoidance of doubt, any macropore volume (pore diameters greater than 50 nm) is not included in the PD n It is not taken into account for the purpose of calculating the value.

[0034] According to the present invention, PD of the porous carbon skeleton 50 The pore size is preferably 4 nm or less, or 3 nm or less, or 2.5 nm or less, or 2 nm or less. 50 The pore size is at least 0.8 nm, or at least 1 nm, or at least 1.2 nm. It is therefore particularly preferred that more than 50% of the total micropore and mesopore volume has micropore morphology.

[0035] More preferably, at least 60% of the total micropore and mesopore volume of the porous carbon skeleton has a pore morphology with a diameter of 5 nm or less. 60 The pore size is preferably 5 nm or less, or 4 nm or less, or 3 nm or less, or 2.5 nm or less, or 2 nm or less, or 1.5 nm or less.

[0036] More preferably, at least 70% of the total micropore and mesopore volume of the porous carbon skeleton has a pore morphology with a diameter of 5 nm or less. 70The pore size is preferably 5 nm or less, or 4 nm or less, or 3 nm or less, or 2.5 nm or less, or 2 nm or less.

[0037] More preferably, at least 80% of the total micropore and mesopore volume of the porous carbon skeleton has a pore morphology with a diameter of 5 nm or less. 80 The pore size is preferably 5 nm or less, or 4 nm or less, or 3 nm or less, or 2.5 nm or less, or 2 nm or less.

[0038] The larger mesopore volume in the porous carbon framework is preferably PD 90 The pore size is restricted to be 20 nm or less, or 15 nm or less, or 12 nm or less, or 10 nm or less, or 8 nm or less, or 6 nm or less, or 5 nm or less, or 4 nm or less, or 3 nm or less, or 2.5 nm or less, or 2 nm or less.

[0039] Preferably, PD 95 The pore size is 20 nm or less, or 15 nm or less, or 12 nm or less, or 10 nm or less.

[0040] According to the invention, the porous carbon skeleton is 50 is 5 nm or less, and PD 90 is 20 nm or less, or PD 50 is 4 nm or less, and PD 90 is 15 nm or less, or PD 50 is 3 nm or less, and PD 90 is 12 nm or less, or PD 50 is 3 nm or less, and PD 90 is 10 nm or less, or PD 50 is 2.5 nm or less, and PD 90 is 10 nm or less, or PD 50 is 2 nm or less, and PD 90 is 8 nm or less, or PD 50 is 2 nm or less, and PD 90 is 6 nm or less, or PD50 is 1.5 nm or less, and PD 90 may be 6 nm or less.

[0041] More preferably, the porous carbon skeleton is PD 50 is 1 nm to 5 nm, and PD 90 is 3nm to 20nm, or PD 50 is 1 nm to 4 nm, and PD 90 is 3nm to 15nm, or PD 50 is 1 nm to 3 nm, and PD 90 is 3nm to 12nm, or PD 50 is 1 nm to 3 nm, and PD 90 is 3nm to 10nm, or PD 50 is 1 nm to 2.5 nm, and PD 90 is 3nm to 10nm, or PD 50 is 1 nm to 2 nm, and PD 90 is 3nm to 8nm, or PD 50 is 1 nm to 2 nm, and PD 90 is 3nm to 6nm, or PD 50 is 1 nm to 2 nm, and PD 90 can be 3 nm to 6 nm.

[0042] A pore fraction having a diameter in the larger mesopore range can be advantageous because it facilitates electrolyte access to the silicon. Thus, pores having diameters in the range of 10 nm to 50 nm (i.e., larger mesopores) can optionally constitute at least 1%, at least 2%, at least 5%, or at least 10% of the total micropore and mesopore volume of the porous carbon scaffold.

[0043] The volume ratio of micropores to mesopores in the porous carbon skeleton can in principle be in the range of 100:0 to 0:100. Preferably, the volume ratio of micropores to mesopores is 90:10 to 55:45, or 90:10 to 60:40, or 85:15 to 65:35.

[0044] The pore size distribution of the porous carbon skeleton can be unimodal, bimodal, or multimodal. The term "pore size distribution" as used herein refers to the distribution of pore sizes relative to the cumulative total internal pore volume of the porous carbon skeleton. A bimodal or multimodal pore size distribution may be preferred, since the proximity of pores with diameters up to 5 nm to larger diameter pores provides the advantage of efficient transport of ions through the porous network to the silicon. Thus, the particulate material has high ion diffusivity, improving the rate performance.

[0045] Optionally, the porous carbon skeleton has a bimodal or multimodal pore size distribution with at least one peak below 2 nm and at least one peak in the range of 5 to 50 nm, preferably with a minimum in the pore size distribution in the range of 5 to 20 nm. More preferably, the porous carbon skeleton has a bimodal or multimodal pore size distribution with at least one peak below 2 nm and at least one peak in the range of 10 to 40 nm, preferably with a minimum in the range of 5 to 15 nm.

[0046] Suitably, the bimodal or multimodal pore size distribution comprises a peak pore size in the micropore range and a peak pore size in the mesopore range that differ from each other by a factor of 5 to 20, more preferably about 10. For example, the porous carbon skeleton may have a bimodal pore size distribution having a peak at a pore size of 2 nm and a peak at a pore size of 20 nm.

[0047] The total volume of micropores and mesopores, as well as the pore size distribution of micropores and mesopores, were determined using quenched solid-state density functional theory (QSDFT) at 77 K for 10°C according to standard methodologies specified in ISO 15901-2 and ISO 15901-3. -6The pore volume and pore size distribution are determined using nitrogen gas adsorption up to a relative pressure of p / p0. Nitrogen gas adsorption is a technique for characterizing the porosity and pore size distribution of a material by condensing a gas in the pores of a solid. As the pressure is increased, the gas condenses initially in the pores with the smallest diameter, until a saturation point is reached where all pores are filled with liquid. The nitrogen gas pressure is then reduced in stages to allow the liquid to evaporate from the system. The pore volume and pore size distribution can be determined by analysis of the adsorption and desorption isotherms and the hysteresis between them. Suitable instruments for measuring the pore volume and pore size distribution by nitrogen gas adsorption include the TriStar II and TriStar II Plus porosity analyzers available from Micromeritics Instrument Corporation, USA, and the Autosorb IQ porosity analyzer available from Quantachrome Instruments.

[0048] Nitrogen gas adsorption is effective for measuring the pore volume and pore size distribution of pores having diameters up to 50 nm, but becomes less reliable for pores of much larger diameters. Therefore, for the purposes of the present invention, nitrogen adsorption is used to determine the pore volume and pore size distribution of only pores having diameters up to 50 nm or less. As mentioned above, P 1 The value of is determined considering only pores with diameters up to 50 nm (i.e., only micropores and mesopores); similarly, PD n The value of is determined for the total volume of micropores and mesopores only.

[0049] Given the limitations of available analytical techniques, it is not possible to measure the pore volume and pore size distribution over the full range of micropores, mesopores, and macropores using a single technique. When the porous carbon skeleton contains macropores, the volume of pores in the range above 50 nm and up to 100 nm is referred to herein as P 2 cm 3 It is specified in terms of the value of / g and is measured by mercury intrusion porosimetry. 2The value relates to the pore volume of the porous carbon skeleton when measured alone, i.e., without any silicon or other material occupying the pores of the porous carbon skeleton.

[0050] To avoid any misunderstanding, P 2 The value of P considers only pores with diameters greater than 50 nm and up to 100 nm. 2 The value of P includes only the volume of macropores with diameters up to 100 nm. Any pore volume measured by mercury intrusion with pore diameters below 50 nm is not included in the P 2 (As discussed above, nitrogen adsorption is used to characterize mesopores and micropores.) The pore volume measured above 100 nm by mercury intrusion is assumed to be the interparticle porosity for the purposes of this invention, and P 2 This pore volume is also not taken into account when determining the value of

[0051] Mercury intrusion porosimetry is a technique for characterizing the porosity and pore size distribution of a material by applying various levels of pressure to a sample of the material immersed in mercury. The pressure required to force mercury into the pores of the sample is inversely proportional to the pore size. Mercury intrusion values ​​reported here were obtained according to ASTM UOP578-11, with a surface tension of mercury at room temperature, γ, of 480 mN / m, and a contact angle, φ, of 140°. The density of mercury at room temperature is 13.5462 g / cm 3 There are many high-precision mercury intrusion instruments available commercially, such as the AutoPore IV series of automated mercury intrusion meters available from Micromeritics Instrument Corporation, USA. For a complete review of mercury intrusion methods, refer to "Analytical Methods in Fine Particle Technology, 1997, Micromeritics Instrument Corporation" by PA Webb and C. Orr (ISBN 0-9656783-0).

[0052] The macropore volume (i.e., P 2The value of P 1 Although some of the macropores may be useful for facilitating electrolyte access to the pore network, the advantages of the present invention are obtained substantially by containing the silicon in the micropores and smaller mesopores.

[0053] Thus, according to the present invention, the total volume of macropores in the porous carbon skeleton is determined by mercury intrusion porosimetry (P 2 cm 3 / g, where P 2 is preferably 0.2 x P 1 Less than or equal to 0.1 x P 1 Less than or equal to 0.05 x P 1 Less than or equal to 0.02 x P 1 Less than or equal to 0.01 x P 1 Less than or equal to 0.005 x P 1 It has the following values:

[0054] In a preferred embodiment, P 2 has a value of 0.3 or less, or 0.25 or less, or 0.20 or less, or 0.15 or less, or 0.1 or less, or 0.05 or less. As discussed above in relation to larger mesopores, a fraction of small pores in the macropore range can be advantageous to facilitate electrolyte access to the silicon.

[0055] The open pore network optionally includes a hierarchical pore structure, ie, a pore structure in which smaller pores branch off from larger pores and the pore sizes have some order.

[0056] It will be understood that intrusion techniques such as gas adsorption and mercury intrusion are only valid for determining the pore volume of pores that are accessible to nitrogen or mercury from the exterior of the porous carbon skeleton. 1 and P 2) should be understood to refer to the volume of open pores, i.e., pores accessible to fluids from outside the porous carbon framework. Completely enclosed pores that cannot be identified by nitrogen adsorption or mercury porosimetry shall not be considered herein in defining porosity values. Similarly, any pore volume located within pores small enough to be below the detection limit by nitrogen adsorption shall not be considered in defining porosity values. 1 is not taken into consideration in determining the value of

[0057] The porous carbon skeleton may comprise crystalline or amorphous carbon, or a mixture of amorphous and crystalline carbon. The porous carbon skeleton may be either a hard or a soft carbon skeleton, and may suitably be obtained by known procedures, including pyrolysis of polymers.

[0058] As used herein, the term "hard carbon" refers to carbon atoms that are primarily distributed in nanoscale polyaromatic domains. 2 It refers to a disordered carbon matrix that adopts a hybridized (three-way bond) state. The polyaromatic domains are cross-linked by chemical bonds, e.g., COC bonds. Because the polyaromatic domains are chemically cross-linked, the hard carbon cannot be converted to graphite at high temperatures. The high G band (approx. 1600 cm) in the Raman spectrum -1 ), hard carbon has graphite-like properties. However, the high D band in the Raman spectrum (approximately 1350 cm -1 ), carbon is not entirely graphite-like.

[0059] The term "soft carbon" as used herein also refers to carbon atoms that are primarily dispersed in polyaromatic domains having dimensions in the range of 5 nm to 200 nm. 2 It refers to a disordered carbon matrix that adopts a hybridized (three-way bond) state. In contrast to hard carbon, the polyaromatic domains in soft carbon are not cross-linked by chemical bonds but are held together by intermolecular forces; that is, at high temperatures, soft carbon can be graphitized. The porous carbon skeleton preferably has at least 50% sp 2For example, the porous carbon skeleton preferably contains 50% to 98% sp 2 Hybrid carbon, 55%-95% sp 2 Hybrid carbon, 60%-90% sp 2 Hybrid carbon, or 70% to 85% sp 2 It may contain hybridized carbon.

[0060] A variety of different materials can be used to create suitable porous carbon scaffolds. Examples of organic materials that can be used include plant biomass, including lignocellulosic materials (coconut shells, rice husks, wood, etc.), and fossil carbon sources such as coal. Examples of polymeric materials that form porous carbon scaffolds upon pyrolysis include phenolic resins, novolac resins, pitch, melamine, polyacrylates, polystyrene, polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), and various copolymers that contain monomer units of acrylates, styrene, α-olefins, vinylpyrrolidone, and other ethylenically unsaturated monomers. Depending on the starting materials and the conditions of the pyrolysis process, a variety of different hard carbon materials are available in the art.

[0061] To increase the mesopore and micropore volume, the porous carbon framework can be subjected to a chemical or gas activation process. Suitable activation processes include contacting the pyrolyzed carbon with one or more of oxygen, steam, CO, CO2, and KOH at temperatures ranging from 600°C to 1000°C.

[0062] Mesopores can also be obtained by known templating processes using extractable pore formers such as MgO and other colloidal or polymeric templates, which can be removed by thermal or chemical means after pyrolysis or activation.

[0063] The porous carbon skeleton is preferably at least 750 mm 2 / g, or at least 1000m 2 / g, or at least 1250m 2 / g, or at least 1500m 2 / g. The term "BET surface area" as used herein should be taken to refer to the surface area per unit mass calculated from measurements of the physical adsorption of gas molecules onto a solid surface using the Brunauer-Emmett-Teller theory according to ISO 9277. Preferably, the BET surface area of ​​the conductive porous particle scaffold is greater than 4000 m 2 / g or less, or 3500m 2 / g or less, or 3250m 2 / g or less, or 3000m 2 / g or less.

[0064] The amount of silicon in the composite particles of the invention is preferably selected such that the silicon occupies no more than about 55% of the internal pore volume of the porous carbon skeleton (in the uncharged state). The silicon preferably occupies about 25% to about 45% of the internal pore volume of the porous carbon skeleton, more preferably about 25% to 40% of the internal pore volume of the porous carbon skeleton. Within these preferred ranges, the pore volume of the porous carbon skeleton is effective to accommodate the expansion of the silicon upon charging and discharging, and excess pore volume that does not contribute to the volumetric capacity of the particulate material is avoided. However, the amount of silicon is also not so high as to prevent effective lithiation due to insufficient metal ion diffusion rate or insufficient expansion volume resulting in mechanical resistance to lithiation.

[0065] The amount of silicon in the porous carbon skeleton is determined by the weight ratio of silicon to the porous carbon skeleton being [0.5 × P 1 ~1.3×P 1 This can be correlated to the effective pore volume by the requirement that the weight ratio of silicon be in the range of 0.1:1. This relationship takes into account the density of silicon and the pore volume of the porous carbon skeleton, and specifies the weight ratio of silicon at which about 20% to 55% of the pore volume is occupied.

[0066] Preferably, the weight ratio of silicon to the porous carbon skeleton is [0.55×P 1 ~1.1×P 1 ]:1 range or [0.6×P1 ~1.1×P 1 ]:1 range or [0.6×P 1 ~1×P 1 ]:1 range or [0.6×P 1 ~0.95×P 1 ]:1 range or [0.6×P 1 ~0.9×P 1 ]:1 range, or [0.65×P 1 ~0.9×P 1 ]:1 range, or [0.65×P 1 ~0.85×P 1 ]:1 range, or [0.65×P 1 ~0.8×P 1 ]:1 range, or [0.7×P 1 ~0.8×P 1 ]:1.

[0067] In some cases, the composite particles may include pores that are completely enclosed and lined with silicon such that the voids are not accessible to the electrolyte.

[0068] Preferably at least 90 wt.%, more preferably at least 95 wt.%, and even more preferably at least 98 wt.% of the silicon mass in the composite particles is located within the interior pore volume of the porous carbon skeleton, such that there is little or no silicon located on the outer surface of the composite particles.

[0069] The particulate material of the invention may be further characterized by its performance by thermogravimetric analysis (TGA) in air: preferably 10% or less, more preferably 5% or less, more preferably 2% or less of the silicon content of the particulate material is unoxidized at 800° C. when the particulate material is analyzed by TGA in air at a temperature ramp rate of 10° C. / min.

[0070] The amount of unoxidized silicon is determined by derivation from TGA traces specific to these materials. A mass increase between about 300 °C and 500 °C corresponds to the initial oxidation of silicon to SiO2, followed by a mass loss between about 500 °C and 600 °C as carbon is oxidized to CO2 gas. Above about 600 °C there is a further mass increase corresponding to the continued conversion of silicon to SiO2, which increases towards an asymptotic value above 1000 °C as the oxidation of silicon becomes complete.

[0071] For the purposes of this analysis, any mass increase above 800°C corresponds to the oxidation of silicon to SiO2, and the total mass at the completion of oxidation is assumed to be SiO2. This allows the fraction of unoxidized silicon at 800°C to be determined as a percentage of the total amount of silicon according to the following formula: Z = 1.875 × [(M f -M 800 ) / M f ]×100% (where Z is the proportion of unoxidized silicon at 800°C, M f is the mass of the sample upon completion of oxidation, and M 800 is the mass of the sample at 800°C).

[0072] Without being bound by theory, it is understood that the temperature at which silicon oxidizes under TGA corresponds roughly to the length scale of the oxide film on silicon, since the diffusion of oxygen atoms through the oxide layer is thermally activated. The size of the silicon nanostructures and their location limit the length scale of the oxide film thickness. It is therefore understood that silicon deposited in micropores and mesopores oxidizes at a lower temperature than silicon deposits on the particle surface, since the oxide film present on these structures is necessarily thinner. Thus, preferred materials according to the invention show substantially complete oxidation of silicon at low temperatures, consistent with the smaller length scale of silicon nanostructures located in micropores and smaller mesopores. For the purposes of the present invention, it is assumed that the oxidation of silicon at 800° C. is silicon on the outer surface of the porous carbon skeleton.

[0073] The silicon is preferably amorphous silicon, which is believed to have better performance as an electroactive material. The morphology of the silicon can be determined by known procedures using X-ray diffraction (XRD).

[0074] The volume of micropores and mesopores in the composite particles (i.e., in the presence of silicon), as measured by nitrogen gas adsorption, is preferably less than 0.15×P 1 Less than or equal to 0.10 x P 1 Less than or equal to 0.05 x P 1 Less than or equal to 0.02 x P 1 The following is the result.

[0075] The weight ratio of silicon to the porous carbon skeleton can be determined by elemental analysis. Elemental analysis is used to determine the weight percentage of both silicon and carbon in the composite particles. Optionally, the amount of hydrogen, nitrogen, and oxygen can also be determined by elemental analysis. Preferably, elemental analysis is also used to determine the weight percentage of carbon (and optionally hydrogen, nitrogen, and oxygen) in the porous carbon skeleton only. Determining the weight percentage of carbon in the porous carbon skeleton only takes into account the possibility that this porous carbon skeleton contains small amounts of heteroatoms in its molecular framework. Both measurements taken together allow for a reliable determination of the weight percentage of silicon in the entire porous carbon skeleton.

[0076] The silicon content is preferably determined by ICP-OES (Inductively Coupled Plasma Optical Emission Spectroscopy). Many ICP-OES instruments are commercially available, such as the iCAP™ 7000 series of ICP-OES analyzers available from ThermoFisher Scientific. The carbon content (and optionally the hydrogen, nitrogen and oxygen content) in the composite particles and in the porous carbon skeleton only is preferably determined by IR absorption. A suitable instrument for determining the carbon, hydrogen, nitrogen and oxygen content is the TruSpec™ Micro elemental analyzer available from Leco Corporation.

[0077] The composite particles preferably have a low total oxygen content. Oxygen may be present in the composite particles, for example, as part of the porous carbon skeleton or as an oxide layer on any exposed silicon surface. The total oxygen content of the composite particles is preferably less than 15% by weight, more preferably less than 10% by weight, more preferably less than 5% by weight, for example less than 2% by weight, or less than 1% by weight, or less than 0.5% by weight.

[0078] The silicon may optionally contain small amounts of one or more dopants. Suitable dopants include boron and phosphorus, other n-type or p-type dopants, nitrogen, or germanium. Preferably, the dopants are present in a total amount of 2% by weight or less, based on the total amount of silicon and dopant(s).

[0079] For the avoidance of doubt, the term "particle size" as used herein refers to the equivalent spherical diameter (esd), i.e., the diameter of a sphere having the same volume as a given particle, where the volume of a particle is understood to include the volume of pores within the particle. 50 " and "D 50 The term "particle size" refers to the median particle size on a volume basis, i.e., the diameter below which 50% by volume of the particle population lies. 10 " and "D 10 The term "particle size" refers to the 10th percentile median particle size on a volume basis, i.e., the diameter below which 10% by volume of the particle population lies. 90 " and "D 90 The term "particle size" refers to the volume-based 90th percentile median particle size, i.e., the diameter below which 90% of the particle population falls, by volume.

[0080] As used herein to define particle size distribution, "D n The term "PD" is used herein to define the pore size distribution, as described above. n " should be distinguished from the term "

[0081] Particle size and size distribution can be determined by conventional laser diffraction techniques according to ISO 13320:2009. Laser diffraction is based on the principle that particles scatter light at angles that vary with the size of the particle, and a collection of particles produces a scattered light pattern defined by intensity and angle that can be correlated to particle size distribution. Many laser diffraction instruments are commercially available for rapid and reliable determination of particle size distribution. Unless otherwise stated, particle size distribution measurements specified or reported herein are measured by a conventional Malvern Mastersizer™ 3000 particle size analyzer manufactured by Malvern Instruments. The Malvern Mastersizer™ 3000 particle size analyzer works by projecting a helium neon gas laser beam through a transparent cell containing particles of interest suspended in an aqueous solution. The light beam that strikes the particle is scattered at an angle that is inversely proportional to the particle size, and a photodetector array measures the light intensity at several predetermined angles, and the intensities measured at the various angles are processed by a computer using standard theoretical principles to determine the particle size distribution. The laser diffraction values ​​reported herein are obtained using a wet dispersion of the particles in distilled water. The refractive index of the particles is assumed to be 3.50 and that of the dispersant is assumed to be 1.330. The particle size distribution is calculated using the Mie scattering model.

[0082] The composite particles are in the range of D 0.5μm to 50μm. 50 Optionally, D 50 The particle size may be at least 1 μm, or at least 2 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm. 50 The particle size may be 40 μm or less, or 30 μm or less, or 25 μm or less, or 20 μm or less, or 15 μm or less.

[0083] For example, the composite particles may have a D in the range of 1 μm to 25 μm, or 1 μm to 20 μm, or 2 μm to 20 μm, or 2 μm to 15 μm, or 3 μm to 15 μm. 50Particles within these size ranges and having the porosity and pore size distribution described herein are ideally suited for use in metal ion battery anodes because they are suitable for forming dense electrode layers that are dispersible in slurries, structurally robust, retain capacity over repeated charge / discharge cycles, and have a uniform thickness in the conventional range of 20 μm to 50 μm.

[0084] Composite particle D 10 The particle size is preferably at least 0.2 μm, or at least 0.5 μm, or at least 0.8 μm, or at least 1 μm, or at least 1.5 μm, or at least 2 μm. 10 Maintaining particle size at or above 0.2 μm reduces the potential for undesirable agglomeration of submicron sized particles, improving dispersibility of the particulate matter and improving volume retention.

[0085] Composite particle D 90 The particle size is preferably 80 μm or less, or 60 μm or less, or 40 μm or less, or 30 μm or less, or 25 μm or less, or 20 μm or less. The presence of very large particles leads to uneven particle packing in the electrode active layer, which hinders the formation of a dense electrode layer, especially an electrode layer having a thickness in the range of 20 μm to 50 μm. Therefore, D 90 The particle size is preferably 40 μm or less, and even smaller is more preferable.

[0086] The composite particles preferably have a narrow particle size distribution span. For example, the particle size distribution span (D 90 -D 10 ) / D 50 (defined as) is preferably 5 or less, more preferably 4 or less, more preferably 3 or less, more preferably 2 or less, and most preferably 1.5 or less. By maintaining a narrow particle size distribution span, efficient packing of the particles into a dense electrode layer can be more easily achieved.

[0087] The composite particles can have a spheroidal shape. Spheroidal particles as defined herein can include both spherical and spheroidal particles, and the shape of the composite particles of the present invention can be preferably defined by reference to the sphericity and aspect ratio of the particles of the present invention. It has been found that spheroidal particles are particularly suitable for dispersion in slurries without forming agglomerates. It has also been found that the use of porous spheroidal particles surprisingly provides additional strength improvements when compared to irregularly shaped porous particles and porous particle fragments.

[0088] The sphericity of an object is conventionally defined as the ratio of the surface area of ​​the object to that of a sphere, where the object and the sphere have the same volume. However, in practice, it is difficult to measure the surface area and volume of individual particles on the micron scale. However, by scanning electron microscopy (SEM) and dynamic image analysis, where the shadow cast by the particle is recorded using a digital camera, highly accurate two-dimensional projection images of micron scale particles can be obtained. The term "sphericity" as used herein shall be understood as the ratio of the area of ​​the particle projection image to the area of ​​a circle, where the particle projection image and the circle have the same circumference. Thus, for an individual particle, the sphericity S is defined as follows:

number

number

[0089] The term "spheroidal" as used herein as applied to the composite particles of the present invention shall be understood to refer to materials having an average sphericity of at least 0.70. The porous spheroidal particles of the present invention preferably have an average sphericity of at least 0.85, more preferably at least 0.90, more preferably at least 0.92, more preferably at least 0.93, more preferably at least 0.94, more preferably at least 0.95. The porous spheroidal particles can optionally have an average sphericity of at least 0.96, or at least 0.97, or at least 0.98, or at least 0.99.

[0090] It will be appreciated that the circumference and area of ​​a two-dimensional particle projection image will depend on the particle orientation for any particle that is not perfectly spheroidal. However, the effect of particle orientation can be countered by reporting the sphericity and aspect ratio as average values ​​obtained from multiple particles with random orientation. Many SEM and dynamic image analyzers are commercially available that can rapidly and reliably determine the sphericity and aspect ratio of particulate matter. Unless otherwise stated, the sphericity values ​​specified or reported herein are measured by a CamSizer XT particle analyzer manufactured by Retsch Technology GmbH. The CamSizer XT is a dynamic image analyzer that can obtain highly accurate distributions of size and shape of particulate matter for sample volumes between 100 mg and 100 g, and properties such as average sphericity and aspect ratio can be calculated directly with this instrument.

[0091] The composite particles of the present invention are preferably 300 mm 2 / g or less, or 250m 2 / g or less, or 200m 2 / g or less, or 150m 2 / g or less, or 100m 2 / g or less, or 80m 2 / g or less, or 60m 2 / g or less, or 40m 2 / g or less, or 30m 2 / g or less, or 25m 2 / g or less, or 20m 2 / g or less, or 15m 2 / g or less, or 10m 2 The BET surface area is preferably at least 0.1 m2 / g. Typically, a small BET surface area is preferred to minimize the formation of a solid electrolyte interfacial (SEI) layer on the surface of the composite particles during the first charge-discharge cycle of an anode comprising the particulate material of the present invention. However, an excessively small BET surface area leads to unacceptably low charge rates and capacities due to the inaccessibility of the bulk of the electroactive material to metal ions in the surrounding electrolyte. For example, the BET surface area is preferably at least 0.1 m2 / g. 2 / g, or at least 1m 2 / g, or at least 2m 2 / g, or at least 5m 2 / g. For example, the BET surface area is 2 / g~25m 2 / g, more preferably 2m 2 / g~15m 2 / g range.

[0092] The particulate material of the present invention typically has a specific charge capacity of 1200 mAh / g to 2340 mAh / g upon initial lithiation. Preferably, the particulate material of the present invention has a specific charge capacity of at least 1400 mAh / g upon initial lithiation.

[0093] The composite particles of the present invention are preferably prepared by chemical vapor infiltration (CVI) of a silicon-containing precursor into the pore structure of a porous carbon skeleton. As used herein, CVI refers to a process in which a gaseous silicon-containing precursor is pyrolyzed on a surface to form elemental silicon and gaseous by-products on the surface.

[0094] Suitable gaseous silicon-containing precursors include silane (SiH4), silane derivatives (e.g., disilane, trisilane, and tetrasilane), and trichlorosilane (SiHCl3). The silicon-containing precursor can be used in pure form or, more commonly, as a dilute mixture with an inert carrier gas such as nitrogen or argon. For example, the silicon-containing precursor can be used in an amount ranging from 0.5% to 20% by volume, or 1% to 10% by volume, or 1% to 5% by volume, based on the total volume of the silicon-containing precursor and the inert carrier gas. The CVI process is preferably carried out at a total pressure of 101.3 kPa (i.e., 1 atm), with a low partial pressure of the silicon precursor, and the remaining partial pressure is brought to atmospheric pressure using an inert padding gas such as hydrogen, nitrogen, or argon. Deposition temperatures in the range of 400° C. to 700° C. are used, for example, 400° C. to 550° C., or 400° C. to 500° C., or 400° C. to 450° C., or 450° C. to 500° C. The CVI process is suitably carried out in a fixed bed reactor, a fluidized bed reactor (including an entrained bed reactor), or a rotary kiln.

[0095] As an example of the fixed bed reactor method, 1.8 g of particulate porous scaffolds were placed on a stainless steel plate with a constant thickness of 1 mm along its length. The plate was then placed inside a 60 mm outer diameter stainless steel tube, and the gas inlet and outlet lines were placed in the hot zone of a retort furnace. The furnace tube was purged with nitrogen gas for 30 minutes at room temperature, after which the sample temperature was increased to 450°C-500°C. The flow rate of nitrogen gas was adjusted to ensure a gas residence time of at least 90 seconds in the furnace tube, and maintained at that rate for 30 minutes. The gas supply was then switched from nitrogen to a mixture of monosilane in nitrogen at a concentration of 1.25% by volume. The monosilane charge was made over a period of 5 hours, with the reactor pressure maintained at 101.3 kPa (1 atm). After the charge was completed, the gas flow rate was kept constant while nitrogen was used to purge the silane from the furnace. The furnace was purged under nitrogen for 30 minutes, and then cooled to room temperature over several hours. The atmosphere is then gradually switched to air over a period of 2 hours by switching the gas flow from nitrogen to air from a compressed air supply.

[0096] The particulate material of the present invention may optionally include a conductive carbon coating. Preferably, the conductive carbon coating may be obtained by a chemical vapor deposition (CVD) method. CVD is a methodology known in the art and involves pyrolysis of a volatile carbon-containing gas (e.g., ethylene) on the surface of the particulate material. Alternatively, the carbon coating may be formed by depositing a solution of a carbon-containing compound on the surface of the particulate material, followed by pyrolysis. The conductive carbon coating has sufficient permeability to allow lithium access to the interior of the composite particle without excessive resistance so as not to degrade the rate performance of the composite particle. For example, the thickness of the carbon coating may preferably be in the range of 2 nm to 30 nm. The carbon coating may optionally be porous and / or may only partially cover the surface of the composite particle.

[0097] The carbon coating has the advantage of further reducing the BET surface area of ​​the particulate material by smoothing out any surface defects and filling any remaining surface microporosity, thereby further reducing first cycle losses, and also improves the electrical conductivity of the composite particle surface, reducing the need for conductive additives in the electrode composition, and also provides an optimal surface for the formation of a stable SEI layer, improving capacity retention upon cycling.

[0098] According to the first aspect of the present invention, there is further provided a particulate material according to the following aspects 1-1 to 1-24.

[0099] Aspect 1-1: (i)P 1 is in the range of 0.7 to 1.4, (ii)PD 50 The pore size is in the range of 0.8 nm to 4 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 1 μm to 18 μm. A particulate material according to a first aspect of the present invention.

[0100] Aspect 1-2: (i)P1 is in the range of 0.7 to 1.4, (ii)PD 50 The pore size is in the range of 0.8 nm to 4 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 1 μm to 12 μm. A particulate material according to a first aspect of the present invention.

[0101] Aspects 1-3: (i)P 1 is in the range of 0.7 to 1.4, (ii)PD 50 The pore size is in the range of 0.8 nm to 4 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 2 μm to 8 μm. A particulate material according to a first aspect of the present invention.

[0102] Aspects 1-4: (i)P 1 is in the range of 0.7 to 1.4, (ii)PD 50 The pore size is in the range of 0.8 nm to 4 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 3 μm to 6 μm. A particulate material according to a first aspect of the present invention.

[0103] Aspects 1-5: (i)P 1 is in the range of 0.7 to 1.1, (ii)PD 50 The pore size is in the range of 1 nm to 2.5 nm, (iii) Porous carbon framework D 50 The particle size is in the range of 1 μm to 18 μm. A particulate material according to a first aspect of the present invention.

[0104] Aspects 1-6: (i)P 1 is in the range of 0.7 to 1.1, (ii)PD 50The pore size is in the range of 1 nm to 2.5 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 1 μm to 12 μm. A particulate material according to a first aspect of the present invention.

[0105] Aspects 1-7: (i)P 1 is in the range of 0.7 to 1.1, (ii)PD 50 The pore size is in the range of 1 nm to 2.5 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 2 μm to 8 μm. A particulate material according to a first aspect of the present invention.

[0106] Aspects 1-8: (i)P 1 is in the range of 0.7 to 1.1, (ii)PD 50 The pore size is in the range of 1 nm to 2.5 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 3 μm to 6 μm. A particulate material according to a first aspect of the present invention.

[0107] Aspect 1-9: (i)P 1 is in the range of 0.7 to 0.9, (ii)PD 50 The pore size is in the range of 1.2 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 1 μm to 18 μm. A particulate material according to a first aspect of the present invention.

[0108] Aspects 1-10: (i)P 1 is in the range of 0.7 to 0.9, (ii)PD 50 The pore size is in the range of 1.2 nm to 2 nm, (iii) D of the porous carbon framework 50The particle size is in the range of 1 μm to 12 μm. A particulate material according to a first aspect of the present invention.

[0109] Aspect 1-11: (i)P 1 is in the range of 0.7 to 0.9, (ii)PD 50 The pore size is in the range of 1.2 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 2 μm to 8 μm. A particulate material according to a first aspect of the present invention.

[0110] Aspect 1-12: (i)P 1 is in the range of 0.7 to 0.9, (ii)PD 50 The pore size is in the range of 1.2 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 3 μm to 6 μm. A particulate material according to a first aspect of the present invention.

[0111] Aspect 1-13: (i)P 1 is in the range of 0.7 to 1.4, (ii)PD 50 The pore size is in the range of 0.8 nm to 4 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 1 μm to 18 μm, (iv) The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.5×P 1 ~1.1×P 1 ]:1, A particulate material according to a first aspect of the present invention.

[0112] Aspect 1-14: (i)P 1 is in the range of 0.7 to 1.4, (ii)PD 50 The pore size is in the range of 0.8 nm to 4 nm, (iii) Porous carbon framework D 50 The particle size is in the range of 1 μm to 12 μm, (iv) The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.5×P 1 ~1.1×P 1 ]:1, A particulate material according to a first aspect of the present invention.

[0113] Aspect 1-15: (i)P 1 is in the range of 0.7 to 1.4, (ii)PD 50 The pore size is in the range of 0.8 nm to 4 nm, (iii) Porous carbon framework D 50 The particle size is in the range of 2 μm to 8 μm, (iv) The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.5×P 1 ~1.1×P 1 ]:1, A particulate material according to a first aspect of the present invention.

[0114] Aspect 1-16: (i)P 1 is in the range of 0.7 to 1.4, (ii)PD 50 The pore size is in the range of 0.8 nm to 4 nm, (iii) Porous carbon framework D 50 The particle size is in the range of 3 μm to 6 μm, (iv) The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.5×P 1 ~1.1×P 1 ]:1, A particulate material according to a first aspect of the present invention.

[0115] Aspect 1-17: (i)P 1 is in the range of 0.7 to 1.1, (ii)PD 50 The pore size is in the range of 1 nm to 2.5 nm, (iii) Porous carbon framework D50 The particle size is in the range of 1 μm to 18 μm, (iv) The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.6×P 1 ~0.9×P 1 ]:1, A particulate material according to a first aspect of the present invention.

[0116] Aspect 1-18: (i)P 1 is in the range of 0.7 to 1.1, (ii)PD 50 The pore size is in the range of 1 nm to 2.5 nm, (iii) Porous carbon framework D 50 The particle size is in the range of 1 μm to 12 μm, (iv) The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.6×P 1 ~0.9×P 1 ]:1, A particulate material according to a first aspect of the present invention.

[0117] Aspect 1-19: (i)P 1 is in the range of 0.7 to 1.1, (ii)PD 50 The pore size is in the range of 1 nm to 2.5 nm, (iii) Porous carbon framework D 50 The particle size is in the range of 2 μm to 8 μm, (iv) The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.6×P 1 ~0.9×P 1 ]:1, A particulate material according to a first aspect of the present invention.

[0118] Aspect 1-20: (i)P 1 is in the range of 0.7 to 1.1, (ii)PD 50 The pore size is in the range of 1 nm to 2.5 nm, (iii) Porous carbon framework D 50The particle size is in the range of 3 μm to 6 μm, (iv) The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.6×P 1 ~0.9×P 1 ]:1, A particulate material according to a first aspect of the present invention.

[0119] Aspect 1-21: (i)P 1 is in the range of 0.7 to 0.9, (ii)PD 50 The pore size is in the range of 1.2 nm to 1.5 nm, (iii) Porous carbon framework D 50 The particle size is in the range of 1 μm to 18 μm, (iv) The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.7×P 1 ~0.8×P 1 ]:1, A particulate material according to a first aspect of the present invention.

[0120] Aspect 1-22: (i)P 1 is in the range of 0.7 to 0.9, (ii)PD 50 The pore size is in the range of 1.2 nm to 1.5 nm, (iii) Porous carbon framework D 50 The particle size is in the range of 1 μm to 12 μm, (iv) The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.7×P 1 ~0.8×P 1 ]:1, A particulate material according to a first aspect of the present invention.

[0121] Aspect 1-23: (i)P 1 is in the range of 0.7 to 0.9, (ii)PD 50 The pore size is in the range of 1.2 nm to 1.5 nm, (iii) Porous carbon framework D 50The particle size is in the range of 2 μm to 8 μm, (iv) The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.7×P 1 ~0.8×P 1 ]:1, A particulate material according to a first aspect of the present invention.

[0122] Aspect 1-24: (i)P 1 is in the range of 0.7 to 0.9, (ii)PD 50 The pore size is in the range of 1.2 nm to 1.5 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 3 μm to 6 μm, (iv) The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.7×P 1 ~0.8×P 1 ]:1, A particulate material according to a first aspect of the present invention.

[0123] It should be understood that, according to the present invention, any preferred / optional features disclosed herein with respect to the first aspect of the invention that are within the scope of the above-mentioned aspects 1-1 to 1-24 should also be considered as preferred / optional features of the above-mentioned aspects 1-1 to 1-24. Similarly, any features of dependent claims that are within the scope of the above-mentioned aspects 1-1 to 1-24 should be construed as if those claims are dependent on the above-mentioned aspects 1-1 to 1-24.

[0124] In a second aspect of the invention, there is provided a composition comprising a particulate material according to the first aspect of the invention and at least one other component. The particulate material used to make the composition of the second aspect of the invention may have any of the features described as preferred or optional in relation to the first aspect of the invention and may be a particulate material according to any of aspects 1-1 to 1-24. In particular, the particulate material of the first aspect of the invention may be used as a component of an electrode composition.

[0125] There is thus provided a composition comprising a particulate material according to the first aspect of the invention and at least one other component selected from (i) a binder, (ii) a conductive additive, and (iii) an additional particulate electroactive material. The composition of the invention is useful as an electrode composition and may thus be used to form an active layer on an electrode.

[0126] The electrode composition may be a hybrid electrode composition comprising the particulate material according to the first aspect of the invention and at least one additional particulate electroactive material. Examples of the additional particulate electroactive material include graphite, hard carbon, silicon, germanium, gallium, aluminum, and lead. The at least one additional particulate electroactive material is preferably selected from graphite and hard carbon. The at least one additional particulate electroactive material is most preferably graphite.

[0127] The at least one additional particulate electroactive material preferably has a diameter in the range of 10 μm to 50 μm, preferably 10 μm to 40 μm, more preferably 10 μm to 30 μm, most preferably 10 μm to 25 μm, for example 15 μm to 25 μm. 50 It has a particle size.

[0128] D of at least one additional particulate electroactive material 10 The particle size is preferably at least 5 μm, more preferably at least 6 μm, more preferably at least 7 μm, more preferably at least 8 μm, more preferably at least 9 μm, and even more preferably at least 10 μm.

[0129] D of at least one additional particulate electroactive material 90 The particle size is preferably 100 μm or less, more preferably 80 μm or less, more preferably 60 μm or less, more preferably 50 μm or less, and most preferably 40 μm or less.

[0130] In a preferred embodiment, the at least one additional particulate electroactive material is selected from carbon-containing particles, graphite particles, and / or hard carbon particles, where the graphite particles and hard carbon particles have a D in the range of 10 μm to 50 μm. 50 More preferably, the at least one additional particulate electroactive material is selected from graphite particles, wherein the graphite particles have a D in the range of 10 μm to 50 μm. 50 It has a particle size.

[0131] The particulate material of the present invention preferably constitutes 0.5% to 80% by weight of the total dry weight of the electroactive material in the electrode composition (i.e. the total dry weight of the particulate material of the present invention and at least one additional particulate electroactive material). More preferably the particulate material of the present invention constitutes 2% to 70% by weight, more preferably 4% to 60% by weight, more preferably 5% to 50% by weight of the total dry weight of the electroactive material in the electrode composition.

[0132] The electrode composition may optionally include a binder. The binder functions to adhere the electrode composition to the current collector and maintain the integrity of the electrode composition. Examples of binders that may be used according to the present invention include polyvinylidene fluoride (PVDF), polyacrylic acid (PAA) and its alkali metal salts, modified polyacrylic acid (mPAA) and its alkali metal salts, carboxymethyl cellulose (CMC), modified carboxymethyl cellulose (mCMC), sodium carboxymethyl cellulose (Na-CMC), polyvinyl alcohol (PVA), alginates and their alkali metal salts, styrene-butadiene rubber (SBR), and polyimides. The electrode composition may include a mixture of binders. Preferably, the binder includes a polymer selected from polyacrylic acid (PAA) and its alkali metal salts, modified polyacrylic acid (mPAA) and its alkali metal salts, SBR, and CMC.

[0133] The binder may suitably be present in an amount of from 0.5% to 20% by weight, preferably from 1% to 15% by weight, and most preferably from 2% to 10% by weight, based on the total dry weight of the electrode composition.

[0134] The binder may optionally be present in combination with one or more additives that modify the properties of the binder, such as crosslinking promoters, coupling agents, and / or adhesion promoters.

[0135] The electrode composition may optionally include one or more conductive additives. Preferred conductive additives are non-electroactive materials that are included to improve electrical conductivity between the electroactive components of the electrode composition and between the electroactive components of the electrode composition and the current collector. The conductive additives may be suitably selected from carbon black, carbon fibers, carbon nanotubes, graphene, acetylene black, ketjen black, metal fibers, metal powders, and conductive metal oxides. Preferred conductive additives include carbon black and carbon nanotubes.

[0136] The one or more conductive additives may suitably be present in a total amount of from 0.5% to 20% by weight, preferably from 1% to 15% by weight, and most preferably from 2% to 10% by weight, based on the total dry weight of the electrode composition.

[0137] In a third aspect, the present invention provides an electrode comprising a particulate material as defined with reference to the first aspect of the invention in electrical contact with a current collector. The particulate material used to prepare the electrode of the third aspect of the invention may have any of the features described as preferred or optional in relation to the first aspect of the invention and may be a particulate matter according to any of aspects 1-1 to 1-24.

[0138] The term current collector as used herein refers to any conductive substrate capable of conducting electrical current to or from the electroactive particles in the electrode composition. Examples of materials that can be used as current collectors include copper, aluminum, stainless steel, nickel, titanium, and sintered carbon. Copper is a preferred material. Current collectors typically have the form of a foil or mesh having a thickness of 3 μm to 500 μm. The particulate material of the present invention can be applied to one or both sides of the current collector, preferably with a thickness ranging from 10 μm to 1 mm, for example, from 20 μm to 500 μm, or from 50 μm to 200 μm.

[0139] Preferably, the electrode comprises an electrode composition as defined with reference to the second aspect of the invention in electrical contact with a current collector. The electrode composition may have any of the features described as preferred or optional in relation to the second aspect of the invention.

[0140] The electrode of the third aspect of the invention may suitably be prepared by combining the particulate material of the invention (optionally in the form of an electrode composition of the invention) with a solvent and optionally one or more viscosity modifying additives to form a slurry. The slurry is then cast onto the surface of a current collector and the solvent is removed to form an electrode layer on the surface of the current collector. Further steps such as heat treatment to harden any binder and / or calendaring the electrode layer may optionally be carried out. The electrode layer suitably has a thickness in the range of 20 μm to 2 mm, preferably 20 μm to 1 mm, preferably 20 μm to 500 μm, preferably 20 μm to 200 μm, preferably 20 μm to 100 μm, preferably 20 μm to 50 μm.

[0141] Alternatively, the slurry can be formed into a free-standing film or mat comprising the particulate material of the present invention, for example, by casting the slurry onto a suitable casting template, removing the solvent, and then removing the casting template. The resulting film or mat has the form of a free-standing agglomerate, which can then be adhered to a current collector by known methods.

[0142] The electrode of the third aspect of the invention can be used as an anode in a metal-ion battery. Thus, in a fourth aspect, the invention provides a rechargeable metal-ion battery comprising an anode comprising an electrode as described above, a cathode comprising a cathode active material capable of releasing and reabsorbing metal ions, and an electrolyte between the anode and the cathode. The particulate material used to make the battery of the fourth aspect of the invention can have any of the features described as preferred or optional in relation to the first aspect of the invention, and can be a particulate material according to any of aspects 1-1 to 1-24.

[0143] The metal ions are preferably lithium ions. More preferably, the rechargeable metal ion battery of the present invention is a lithium ion battery and the cathode active material is capable of releasing lithium ions.

[0144] The cathode active material is preferably a metal oxide-based composite material. Examples of suitable cathode active materials include LiCoO2, LiCo 0.99 Al 0.01 O2, LiNiO2, LiMnO2, LiCo 0.5 Ni 0.5 O2, LiCo 0.7 Ni 0.3 O2, LiCo 0.8 Ni 0.2 O2, LiCo 0.82 Ni 0.18 O2, LiCo 0.8 Ni 0.15 Al 0.05 O2, LiNi 0.4 Co 0.3 Mn 0.3 O2 and LiNi 0.33 Co 0.33 Mn 0.34 O2. The cathode current collector usually has a thickness of 3 μm to 500 μm. Examples of materials that can be used as the cathode current collector include aluminum, stainless steel, nickel, titanium, and sintered carbon.

[0145] The electrolyte is preferably a non-aqueous electrolyte containing a metal salt, such as a lithium salt, and may include, but is not limited to, a non-aqueous electrolyte, a solid electrolyte, and an inorganic solid electrolyte. Examples of non-aqueous electrolytes that may be used include aprotic organic solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma butyrolactone, 1,2-dimethoxyethane, 2-methyltetrahydrofuran, dimethylsulfoxide, 1,3-dioxolane, formamide, dimethylformamide, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, sulfolane, methylsulfolane, and 1,3-dimethyl-2-imidazolidinone.

[0146] Examples of organic solid electrolytes include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate ester polymers, polyester sulfides, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ionically dissociable groups.

[0147] Examples of inorganic solid electrolytes include nitrides, halides, and sulfides of lithium salts, such as Li5NI2, Li3N, LiI, LiSiO4, Li2SiS3, Li4SiO4, LiOH, and Li3PO4.

[0148] The lithium salt is preferably soluble in the selected solvent or mixture of solvents. Examples of suitable lithium salts include LiCl, LiBr, LiI, LiClO4, LiBF4, LiBC4O8, LiPF6, LiCF3SO3, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, and CF3SO3Li.

[0149] When the electrolyte is a non-aqueous organic solution, the metal ion battery preferably includes a separator inserted between the anode and the cathode. The separator is typically formed of an insulating material having high ion permeability and high mechanical strength. The separator typically has a pore size of 0.01 μm to 100 μm and a thickness of 5 μm to 300 μm. An example of a suitable electrode separator is a microporous polyethylene film.

[0150] The separator may be replaced with a polymer electrolyte material, in which case the polymer electrolyte material is present in both the composite anode layer and the composite cathode layer. The polymer electrolyte material may be a solid polymer electrolyte or a gel-type polymer electrolyte.

[0151] In a fifth aspect, the present invention provides the use of a particulate material as defined with reference to the first aspect of the invention as an anode active material. Preferably, the particulate material has the form of an electrode composition as defined with reference to the second aspect of the invention, and most preferably the electrode composition comprises one or more additional particulate electroactive materials as defined above. The particulate material used according to the fifth aspect of the invention may have any of the features described as preferred or optional in relation to the first aspect of the invention and may be a particulate material according to any of aspects 1-1 to 1-24. [Brief description of the drawings]

[0152] [Figure 1] FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES

[0153] Carbon skeleton particles with the following characteristics were used to prepare the particulate composite materials in Table 1. 1860m 2 BET surface area / g 0.88cm 3 / g P 1 Pore ​​volume Microporosity (micropore volume / (micropore volume + mesopore volume)) of 54% 1.4nm PD 50 , 5.1nm PD 90 , 0.60nm PD 10 , 0.87nmPD 30 , and 2.79 nm PD 75 D of 1.31 μm 10 D of ~11.1 μm 90 D of 3.12 μm 50 Particle size

[0154] Si-C complex: The Si-C composite material produced by the method described herein has the properties shown in Table 1 below. The silicon-carbon composite material was synthesized in a vertical bubbling fluidized bed reactor equipped with a stainless steel cylindrical vessel with an inner diameter of 83 mm. A powder of carbon skeleton particles having the above-mentioned properties is placed in the reactor in an amount of 250 g. An inert gas (nitrogen) is injected into the reactor at a low flow rate to remove oxygen. The reactor is then heated to a reaction temperature of 400°C to 500°C, and 4 v / v % monosilane gas diluted with nitrogen is fed into the bottom of the reactor at a flow rate sufficient to fluidize the carbon skeleton particles and for a length of time sufficient to deposit the target mass of silicon.

[0155] [Table 1]

[0156] Electrode preparation Anodes and test cells incorporating the particulate Si-C composites of Table 1 were fabricated using the following method.

[0157] Test coin cells were fabricated with a negative electrode containing the silicon-based material prepared as described above. A dispersion of Carbon Super P (conductive carbon) and CMC binder was mixed in a Thinky™ mixer. The silicon-based material was added to the mixture and mixed in the Thinky™ mixer for 30 minutes. SBR binder was then added to achieve a CMC:SBR ratio of 1:1 to obtain a slurry with a weight ratio of silicon-based material:CMC / SBR:conductive carbon of 70%:16%:14%. The slurry was mixed in the Thinky™ mixer for an additional 30 minutes and then coated on a 10 μm thick copper substrate (current collector), dried at 50° C. for 10 minutes, and then further dried at 110° C. for 12 hours to form an electrode with an active layer on the copper substrate.

[0158] Cell Manufacturing and Cycle Full cell manufacturing A full coin cell was fabricated using a circular negative electrode with a radius of 0.8 cm cut from the above electrode along with a porous polyethylene separator and a nickel manganese cobalt (NMC532) positive electrode. The positive and negative electrodes were designed to form a balanced pair such that the target capacity ratio of these electrodes was approximately 0.9. An electrolyte containing 1M LiPF6 in a 7:3 EMC / FEC (ethyl methyl carbonate / fluoroethylene carbonate) solution containing 3 wt% vinylene carbonate was then added to the cell before sealing.

[0159] For each composite, three coin cells were fabricated.

[0160] The full coin cell was cycled as follows: the anode was lithiated by applying a constant current at a rate of C / 25 with a cutoff voltage of 4.3V. Once the cutoff voltage was reached, a constant voltage of 4.3V was applied until a cutoff current of C / 100 was reached. The cell was then allowed to rest for 10 minutes in the lithiated state. The anode was then delithiated with a constant current of C / 25 with a cutoff voltage of 2.75V. The cell was then allowed to rest for 10 minutes. After this initial cycle, the anode was lithiated with a constant current of C / 2 with a cutoff voltage of 4.3V, followed by a constant voltage of 4.3V with a cutoff current of C / 40 and a rest time of 5 minutes. The anode was then delithiated with a constant current of C / 2 with a cutoff voltage of 2.75V. This was then repeated for the desired number of cycles.

[0161] The charge (lithiation) and discharge (delithiation) capacities for each cycle are calculated per unit mass of silicon-carbon composite, and the capacity retention is calculated for each discharge capacity as a percentage of the second cycle discharge capacity. The first cycle loss (FCL) is (1-(first delithiation capacity / first lithiation capacity)) x 100%. Key values ​​averaged across three coin cells for each material are shown in the table below, and the capacity retention of all six cells is plotted in Figure 1.

[0162] From Table 2 below and Figure 1, it can be demonstrated that cells made with Sample A material have very consistent cycling performance with higher capacity retention than cells made with Sample B material, which also has variability in performance.

[0163] [Table 2]

Claims

1. A particulate material comprising a plurality of composite particles, the composite particles comprising: (a) a porous carbon framework containing micropores and / or mesopores, The micropores and / or mesopores have a total pore volume of P 1 cm 3 / g, where P 1 is in the range of 0.7 to 1.2, and P.D. 50 The pore diameter is 1 nm to 2.5 nm, and PD 90 The pore diameter is 3 nm to 10 nm, a porous carbon framework, wherein the total pore volume of the micropores and mesopores and the PD 50 pore diameter are measured by nitrogen gas adsorption at 77K up to a relative pressure p / p 0 of 10 −6 using Quenched Solid Density Functional Theory (QSDFT) according to ISO 15901-2 and ISO 15901-3; (b) a plurality of elemental nanoscale silicon domains located within the micropores and / or mesopores of the porous carbon framework; Including, The weight ratio of silicon to the porous carbon skeleton in the composite particle is [0.5×P 1 ~1.3 x P 1 ]: 1, and the composite particles have a D in the range of 1 μm to 25 μm. 50 A particulate material having a particle size.

2. P 1 2. The particulate material of claim 1 , wherein R has a value of at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least 1, or at least 1.05, or at least 1.

1.

3. P 1 3. The particulate material according to claim 1 or 2, wherein R has a value of 1.1 or less, or 1.0 or less, or 0.9 or less.

4. The PD of the porous carbon skeleton 50 A particulate material according to any one of claims 1 to 3, wherein the pore size is 2 nm or less, or 1.5 nm or less.

5. The PD of the porous carbon skeleton 60 The particulate material according to any one of claims 1 to 4, wherein the pore size is 5 nm or less.

6. The PD of the porous carbon skeleton 70 The particulate material according to any one of claims 1 to 5, wherein the pore size is 5 nm or less.

7. The PD of the porous carbon skeleton 80 The particulate material according to any one of claims 1 to 6, wherein the pore size is 5 nm or less.

8. The PD of the porous carbon skeleton 90 8. A particulate material according to any one of the preceding claims, wherein the pore size is 8 nm or less, or 6 nm or less, or 5 nm or less, or 4 nm or less.

9. The PD of the porous carbon skeleton 95 9. A particulate material according to any one of the preceding claims, wherein the pore size is 20nm or less, or 15nm or less, or 12nm or less, or 10nm or less.

10. A particulate material according to any one of claims 1 to 9, wherein the porous carbon skeleton has a unimodal pore size distribution.

11. A particulate material according to any one of claims 1 to 9, wherein the porous carbon skeleton has a bimodal or multimodal pore size distribution.

12. 12. The particulate material of claim 11, wherein the porous carbon skeleton has a bimodal or multimodal pore size distribution with at least one peak below 2 nm and at least one peak in the range of 5 nm to 50 nm.

13. 13. The particulate material of claim 12, wherein the porous carbon skeleton has a bimodal or multimodal pore size distribution with at least one peak below 2 nm and at least one peak in the range of 10 nm to 40 nm.

14. The porous carbon skeleton has a diameter in the range of more than 50 nm to 100 nm and a total volume of P 2 cm 3 / g, where P 2 is 0.2 x P 1 or less than 0.1 x P 1 Less than or equal to 0.05 x P 1 or less than 0.02 x P 1 or less than 0.01 x P 1 Less than or equal to 0.005 x P 1 A particulate material according to any one of claims 1 to 13, wherein:

15. The weight ratio of silicon to the porous carbon skeleton is [0.55×P 1 ~1.1 x P 1 ]: range of 1, or [0.6 × P 1 ~1.1 x P 1 ]: range of 1, or [0.6 × P 1 ~1xP 1 ]: range of 1, or [0.6 × P 1 ~0.95 x P 1 ]: range of 1, or [0.6 × P 1 ~0.9 x P 1 ]: range of 1, or [0.65 × P 1 ~0.9 x P 1 ]: range of 1, or [0.65 × P 1 ~0.85 x P 1 ]: range of 1, or [0.65 × P 1 ~0.8 x P 1 ]: range of 1, or [0.7 x P 1 ~0.8 x P 1 ]:

1. The particulate material according to any one of claims 1 to 14.

16. 16. A particulate material according to any preceding claim, wherein at least some of the micropores and / or mesopores comprise voids completely surrounded by silicon.

17. A particulate material according to any preceding claim, wherein at least 90% by weight of the silicon mass in the composite particles is located in the interior pore volume of the porous carbon skeleton.

18. When the particulate material is analyzed by TGA in air at a temperature ramp rate of 10° C. / min, the following equation is obtained: Z=1.875×[(M f −M 800 ) / M f ]×100% (where Z is the fraction of unoxidized silicon at 800° C., M f is the mass of the sample at the completion of oxidation, and M 800 is the mass of the sample at 800° C.) 18. A particulate material according to any one of the preceding claims, wherein no more than 10% of the silicon content of the particulate material is unoxidized at 800°C, as determined according to

19. The composite particles have a D of at least 2 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm. 50 A particulate material according to any one of claims 1 to 18, having a particle size.

20. The composite particles have a D of 20 μm or less, or 15 μm or less. 50 A particulate material according to any one of claims 1 to 19 having a particle size.

21. The composite particles have a D of at least 0.2 μm, or at least 0.5 μm, or at least 0.8 μm, or at least 1 μm, or at least 1.5 μm, or at least 2 μm. 10 A particulate material according to any one of claims 1 to 20, having a particle size.

22. The composite particles have a D of 80 μm or less, or 60 μm or less, or 40 μm or less, or 30 μm or less, or 25 μm or less, or 20 μm or less. 90 A particulate material according to any one of claims 1 to 21 having a particle size.

23. 23. The particulate material of any one of the preceding claims, wherein the composite particles have a particle size distribution span of 5 or less, or 4 or less, or 3 or less, or 2 or less, or 1.5 or less.

24. The composite particles are 300 mm 2 / g or less, or 250m 2 / g or less, or 200m 2 / g or less, or 150m 2 / g or less, or 100m 2 / g or less, or 80m 2 / g or less, or 60m 2 / g or less, or 40m 2 / g or less, or 30m 2 / g or less, or 25m 2 / g or less, or 20m 2 / g or less, or 15m 2 24. The particulate material of any one of the preceding claims, having a BET surface area of ​​no more than 1 / g.

25. The composite particles are at least 0.1 m 2 / g, or at least 1 m 2 / g, or at least 2m 2 / g, or at least 5m 2 25. The particulate material according to any one of claims 1 to 24, having a BET surface area of ​​1 / g.

26. The volume of the micropores and mesopores of the composite particles measured by nitrogen gas adsorption is 0.15×P 1 or less than 0.10 x P 1 Less than or equal to 0.05 x P 1 or less than 0.02 x P 1 26. A particulate material according to any one of claims 1 to 25, wherein:

27. 27. The particulate material according to any one of claims 1 to 26, having a specific capacity when lithiated of from 1200 mAh / g to 2340 mAh / g.

28. A composition comprising a particulate material according to any one of claims 1 to 27 and at least one other ingredient.

29. 29. The composition of claim 28 comprising the particulate material of any one of claims 1 to 27 and at least one other component selected from: (i) a binder; (ii) a conductive additive; and (iii) an additional particulate electroactive material.

30. 30. The composition according to claim 28 or 29, comprising from 1 wt% to 95 wt%, or from 2 wt% to 90 wt%, or from 5 wt% to 85 wt%, or from 10 wt% to 80 wt%, of the particulate material according to any one of claims 1 to 26, based on the total dry weight of the composition.

31. 31. The composition of claim 29 or 30, comprising at least one additional particulate electroactive material.

32. 32. The composition of claim 31 , wherein the at least one additional particulate electroactive material is selected from graphite, hard carbon, silicon, tin, germanium, gallium, aluminum, and lead.

33. 33. The composition of any one of claims 29 to 32, comprising a binder in an amount of 0.5% to 20% by weight, or 1% to 15% by weight, or 2% to 10% by weight, based on the total dry weight of the composition.

34. 34. The composition of any one of claims 29 to 33, comprising the one or more conductive additives in a total amount of from 0.5 wt.% to 20 wt.%, or from 1 wt.% to 15 wt.%, or from 2 wt.% to 10 wt.%, based on the total dry weight of the composition.

35. 28. An electrode comprising a particulate material according to any one of claims 1 to 27 in electrical contact with a current collector.

36. 36. An electrode as claimed in claim 35, wherein the particulate material has the form of a composition as claimed in any one of claims 28 to 34.

37. (i) an anode comprising the electrode of claim 35 or 36; (ii) a cathode comprising a cathode active material capable of releasing and reabsorbing metal ions; (iii) an electrolyte between the anode and the cathode; A rechargeable metal ion battery comprising:

38. Use of a particulate material according to any one of claims 1 to 27 as an anode active material.

39. The use according to claim 38, wherein the particulate material has the form of a composition according to any one of claims 28 to 34.

Citation Information

Patent Citations

  • Lithium secondary battery

    JP2003100284A

  • Composite and method for producing the same

    JP2016132608A

  • Composite carbon materials comprising lithium alloying electrochemical modifiers

    US20140272592A1

  • A method of fabricating fibres composed of silicon or a silicon-based material and their use in lithium rechargeable batteries

    WO2007083155A1

  • Novel materials with extremely durable intercalation of lithium and manufacturing methods thereof

    WO2017040299A1